2018
DOI: 10.3390/a11110176
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Verbal Decision Analysis Paradigm for Implementable Prioritization of Software Requirements

Abstract: The activity of prioritizing software requirements should be done as efficiently as possible. Selecting the most stable requirements for the most important customers of a development company can be a positive factor considering that available resources do not always encompass the implementation of all requirements. There are many quantitative methods for prioritization of software releases in the field of search-based software engineering (SBSE). However, we show that it is possible to use qualitative verbal d… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…In previous work [9][10][11] we have obtained satisfactory results using VDA as a means to select and order requirements in a software development project. In order to corroborate our results of previous studies, we look for other methods to verify the efficiency proposed by this research.…”
Section: Orcon Methodologymentioning
confidence: 95%
See 4 more Smart Citations
“…In previous work [9][10][11] we have obtained satisfactory results using VDA as a means to select and order requirements in a software development project. In order to corroborate our results of previous studies, we look for other methods to verify the efficiency proposed by this research.…”
Section: Orcon Methodologymentioning
confidence: 95%
“…In previous researches [9][10][11][12], we had good results when we compared the results generated by the Zapros III-i method concerning the SBSE methods. In these works, it was reported that the VDA method is no better than the SBSE methods, but the gain of this research is the opening of this new front in the VDA field, leaving this field as an alternative nonexistent to select and prioritize software requirements.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations